Copper - Kibuishi, Kazu, 1978- (New York : Graphix, 2010)
A collection of webcomics from Kazu Kibuishi that chronicle the adventures of Copper, a curious and imaginative boy, and Fred, his fearful dog.
Wilson's Children, October 2010.
Wilson's Junior High School, October 2010.
School Library Journal, May 2010.
Booklist, December 2009.
Horn Book, October 2010.
Voice of Youth Advocates (V.O.Y.A.), February 2010.
Keywords: Boys -- Comic books, strips, etc. -- Juvenile fiction; Dogs -- Comic books, strips, etc. -- Juvenile fiction; Human-animal relationships -- Comic books, strips, etc. -- Juvenile fiction; Boys -- Fiction; Dogs -- Fiction; Human-animal relationships -- Fiction; Adventure and adventurers -- Fiction; Cartoons and comics; Boys -- Comic books, strips, etc -- Fiction; Dogs -- Comic books, strips, etc -- Fiction; Human-animal relationship -- Comic books, strips, etc -- Fiction; Adventure graphic novels; Comic books, strips, etc; Friendship -- Fiction; Imagination -- Fiction; Adventure fiction; Graphic novels; Comics (Graphic works)